The immunity solution : seven weeks to living healthier and longer - Nissola, Leo (Countryman Press, an imprint of W.W. Norton & Company, 2023)
"Optimize your natural defenses with this essential, science-based guide and its simple program of practical strategies to help support your immune system. In this must-read book, immunologist Leo Nissola provides a comprehensive overview of your body's defenses, revealing what can cause problems, how to recognize warning signs, and how to fight back. Every day, bacteria, viruses, and other germs attack you, but you stay healthy most of the time. While you can't live forever, there's more to fighting disease than you might think, including diet, lifestyle habits, and environment. Nissola explains why improving your natural defenses should be at the top of your health priorities, and he details the cutting-edge treatments that researchers are developing to hack the immune system. He explores the latest science on immune-boosting diets, supplements, and longevity while debunking myths about antibodies, inflammation, and why some people rarely get sick. Featuring an easy, step-by-step program, this information-packed handbook will help you support your body's defenses, ward off aging, and maximize your health every day"--